a)3(x-1)(x+4)-2(xla a doua-5) b)(x+5)(6x-1)+24x la a patra(-4x la a doua)
MFM:
Notezi asa:
Răspunsuri la întrebare
Răspuns de
2
a)3(x-1)(x+4)-2(x²-5)=
3(x²+4x-x-4)-2x²+10=
3(x²+3x-4)-2x²+10=
3x²+9x-12-2x²+10=
x²+9x-2
b)(x+5)(6x-1)+24x⁴-4x²=
6x²-x+30x-5+24x⁴-4x²=
24x⁴+2x²-x-5
3(x²+4x-x-4)-2x²+10=
3(x²+3x-4)-2x²+10=
3x²+9x-12-2x²+10=
x²+9x-2
b)(x+5)(6x-1)+24x⁴-4x²=
6x²-x+30x-5+24x⁴-4x²=
24x⁴+2x²-x-5
Răspuns de
0
A))
(3x-3)(x+4)-2x^2+10
= 3x^2+9x-12 -2x^2+10
= x^2 +9x-2
B))
= 6x^2+29x-5-96x^6
(3x-3)(x+4)-2x^2+10
= 3x^2+9x-12 -2x^2+10
= x^2 +9x-2
B))
= 6x^2+29x-5-96x^6
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă